A Quantitative Approach to Employment Planning - Nemhauser, George L.; Nuttle, Henry L. W. (Management Science, 1965)
A model is developed for planning the intake of employees as a function of time in the face of varying demand for service. The problem is complicated by resignations which, in part, depend on the intake. The model is solved by dynamic programming using a form of successive approximations to circumvent the computational difficulty of high state variable dimensionality. The model is presented in the context of a real situation for which the results have been successfully implemented.